Comparison between dark and illuminated annealing of compensated and uncompensated mc-Si wafers - Wyller, Guro Marie; Wiig, Marie Syre; Thomassen, Bent; Søndenå, Rune (AIP conference proceedings, 2022)
Minority carrier lifetime degradation in crystalline silicon wafers is a topic of high technological importance and have been subject to an active research effort in the latest years. Recently, annealing wafers in the dark have been shown to cause degradation and regeneration of the carrier lifetime over time, similarly to the much-studied light and elevated temperature induced degradation (LeTID). In this work, we study and compare degradation and subsequent regeneration behavior during illuminated as well as dark annealing of p-type HPMC-Si wafers with different resistivity and compensation level. During both illuminated and dark annealing, we find that the degradation extent is lower in samples with lower resistivity, i.e. that the degradation extent is reduced with an increasing density of doping atoms. The rate of degradation and regeneration is not altered by differences in resistivity. With increased compensation level, we observe a decrease in degradation extent combined with a reduction of degradation and regeneration rates. The differences in degradation and regeneration rates are much more pronounced during dark anneal than during annealing with illumination.